Arteriovenous fistula between the right internal mammary artery and the subclavian vein: percutaneous closure with detachable ballooncatheter embolization - Moura, Regina [UNESP]; Uflacker, R.; Yoshida, Winston Bonetti [UNESP]; Rollo, Hamilton Almeida [UNESP]; Lastoria, S.; Maffei, Francisco Humberto de Abreu [UNESP] (My University, 1993)
A case of iatrogenic fistula from the right internal mammary artery to the subclavian vein following subclavian vein catheterization is reported. The patient had undergone percutaneous Intracath catheterization of the subclavian vein to treat hypovolemic shock during the surgical treatment of ectopic pregnancy. She had remained symptom-free for 7 years and then started to complain of effort dyspnea. The patient was found to have a thrill and a bruit at the subclavian region, and arteriography demonstrated a fistula between the right internal mammary artery and the subclavian vein. The fistula was successfully closed by embolization with a percutaneous detachable balloon catheter. © 1993.
Keywords: arteriovenous fistula; catheterization; subdavian vein; adult; angiography; artificial embolism; balloon dilatation; case report; ectopic pregnancy; female; human; iatrogenic disease; injury; instrumentation; mammary artery; postoperative complication; pregnancy; radiography; subclavian vein; Adult; Angiography; Arteriovenous Fistula; Balloon Dilatation; Case Report; Embolization, Therapeutic; Female; Human; Iatrogenic Disease; Mammary Arteries; Postoperative Complications; Pregnancy; Pregnancy, Ectopic; Subclavian Vein